Daya Hambat Ekstrak Teripang Emas (Stichopus hermanii) terhadap Bakteri Enterococcus faecalis - Roy Tamara; Linda Rochyani; Paulus Budi Teguh (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2015)
Background: Enterococcus faecalis is one caused bacteria of root canal infections. ChKM is mostly used as sterilization agent in endodontic treatment. Stichopus hermanii extract has been reported to have antibacterial effects for gram-negative and gram-positive bacteria, so could be potentially developed as a root canal sterilization agent. Purpose: The aim of this study was to determine the inhibitory effect of Stichopus hermanii extract on Enterococcus faecalis bacteria. Materials and Methods: This study was an experimental study with post test only control group design and were tested by diffusion methods with 4 groups concentration of 2,5%, 3%, 3,5%, 4%, and 2 controls groups using DMSO 1% as negative control, and ChKM as positive control, each group consisted of 7 samples. The inhibition effect were examined by measure the diameter of the clear zone around the disc. Data were analyzed by one way ANOVA test and followed by LSD test. Results: Results showed that the mean of inhibition zone at concentrations of 2,5% (7,3543 mm), 3% (8,1086 mm), 3,5% (8,7286 mm), 4% (9,4029 mm), DMSO 1% (6,0257 mm) and ChKM (25,49 mm). It had been proved that. Stichopus hermanii extract could inhibit the growth of Enterococcus faecalis (p<0,05). The largest diameter of the clear zone was in the concentration of 4%. Conclusion: Stichopus hermanii extract could inhibit the growth of Enterococcus faecalis and the most effective inhibitory concentration is 4%.